Does Preoperative Thrombocytopenia in Patients Undergoing Robotic Hepatectomy for Liver Tumors Predict Poor Outcomes? A Propensity-Score Match Analysis. Issue 8 (August 2022) - Crowley, Marci; Rayman, Shlomi; Ross, Sharona; Crespo, Kaitlyn; Syblis, Cameron; Sucandy, Iswanto; Rosemurgy, Alexander
Introduction: Thrombocytopenia is a known surrogate marker for cirrhosis and portal hypertension and has been associated with increased risk of poor perioperative outcomes when studied in "open" operations. This study was undertaken to assess thrombocytopenia as an independent risk factor for undesirable perioperative outcomes after robotic hepatectomy. Methods: We retrospectively reviewed 279 patients who underwent robotic hepatectomy at our institution. Patients were stratified into two cohorts based on preoperative platelet counts. Thrombocytopenia was classified as having a platelet count less than 150 /μL. Patients were 2:1 ratio propensity-score matched based on IWATE score and age. Data are presented as median (mean ± SD). Results: Thirty-six patients with thrombocytopenia were matched to 72 patients without thrombocytopenia. Patients with thrombocytopenia had higher MELD scores [p = 0.02] and higher Child-Pugh Scores [p <0.001]. Intraoperatively, patients with thrombocytopenia had shorter operative duration [p = 0.03] but similar estimated blood loss (EBL) [p = 0.78]. Postoperatively, there were more fresh frozen plasma transfusions in patients with thrombocytopenia [p = 0.04]. There were no differences in IWATE scores, tumor size, conversions to "open" operations, intraoperative complications, patient length of stay (LOS), Clavien-Dindo score ≥ III complications, perioperative RBC transfusion, in-hospital mortality, or 30-day readmissions. Conclusions: In our propensity-score matched study, patients with thrombocytopenia had more severe liver disease; however, there were no differences in their EBL, LOS, or perioperative complications. Preoperative thrombocytopenia, while being an indicator of severity of liver disease potentially promoting perioperative bleeding, does not negatively affect the perioperative course of patients undergoing robotic hepatectomy.